The complete mitochondrial genome of the hybrid of Jersey cattle (Bos taurus; ♂) × Gannan yak (Bos grunniens; ♀) - Guo, Xian (Mitochondrial DNA B Resour, 2019)
In this study, we reconstructed the complete mitochondrial genome of the hybrid of Jersey cattle (Bos taurus; ♂) × Gannan yak (Bos grunniens; ♀) from Illumina sequencing reads. The mitochondrial genome is 16,322 bp in length with an A + T-biased nucleotide composition, and encodes 13 protein-coding genes, 22 tRNAs, and 2 rRNAs along with a noncoding control region. In addition, its gene order is identical to those of previously published mitochondrial genomes of the genera Bison and Bos. Phylogenetic analysis indicates that this hybrid is most closely related to Gannan yak and Jinchuan yak.